POTENSI SERAT BATANG (BAST FIBERS) SEBAGAI PENGUAT BIOKOMPOSIT UNTUK APLIKASI OTOMOTIF - Alaya F.H. Mukhammad (TRAKSI, 2013)
The Neseccary of material which is light, cheap and environment friendly make biocomposite that reinforced natural fiber as alternative material forautomotive components. Non-wood natural fiber is classified into 5 groups: bast ﬁbers, leaf ﬁbers, seed fibers, straw fibers and grass fibers. Bast fibers has a high potential as a reinforced in biocomposite because it has some variaties, abundant resources and high mechanical properties. Nowadays, bast fibers has been used by automotive manufacturer in Europe as interior components and begin to be developed for exterior components. Natural characteristic of hydrophilic is the major problem in biocomposite. The water contents in natural fiber will decrease interface bonding between fiber and matrix, so that produce low mechanical properties of biocomposite. Alkali fiber surface treatment improve interface bonding between fiber and matrix and clean the extractivemedia from natural fiber as lignin, wax and dust, so that produce fiber whose surface has the uniform topography.